COMPUTER ALGORITHMS SYMINV: AN ALGORITHM FOR THE INVERSION OF A POSITIVE DEFINITE MATRIX BY THE CHOLESKY DECOMPOSITION. - Seaks, Terry (Econometrica)
The article focuses on the SYMINV computer algorithm that inverts a symmetric positive definite matrix through the Cholesky decomposition. The FORTRAN IV computer language has been used to present a numerical analysis of the SYMINV computer algorithm. Significantly, computational formulas have been formulated.